Turn-key research in food processing and manufacturing for reducing the impact of climate change - Martindale, Wayne; Hollands, Tom Æ.; Jagtap, Sandeep; Hebishy, Essam; Duong, Linh (Wiley, 2023)
This study addresses the critical need to report original and current findings on the global food system's ability to meet the growing natural resource demands of an estimated 9 billion global population. The objective is to provide guidance for researchers in developing strategies to reduce climate change risks in the food and beverage supply. To achieve this, we propose integrating innovative industry insights and digital applications into existing food system models as industrial demonstrators. Our research encompasses six impactful themes, demonstrating effective delivery methodologies. We highlight that human-centred activities and practices, often overlooked in sustainability assessments, hinder improved security and sustainability in the food system. Through our work, we showcase how smarter food production processes, along with active citizen engagement, can achieve desired outcomes outlined in frameworks, such as the Sustainable Development Goals. A crucial aspect is the development of Internet of Things (IoT) platforms, integrating workforce practices into manufacturing activities, and driving the necessary cultural changes for a sustainable food system. This study illuminates challenges faced by the global food system and provides actionable insights and methodologies to guide researchers and industry stakeholders in creating a more sustainable and secure future for food production and consumption.
Keywords: climate change impact; food security; global food system; Internet of Things (IoT); smarter food production processes; sustainability assessments; sustainable development goals